INNOVATION IN EDUCATIONAL DEVELOPMENT: INTERFACE DESIGN AND USER EXPERIENCE AS THE KEY TO THE SUCCESS OF VIRTUAL LABORATORIES IN MODERN EDUCATION - Dewi Rulia Sitepu; Khairina Afni; Inggrid Puji Astri Purba; Ika Febriana; A Akrim; Amiruddin Amiruddin (BEST Journal (Biology Education, Sains and Technology), 2026)
Virtual laboratories (VL) have emerged as innovative solutions to overcome the limitations of traditional practical work in modern education. This research examines the critical role of user interface (UI) and user experience (UX) design in determining the success of virtual laboratory implementation. Through a systematic literature review of publications from 2020-2025, we analyze how user-centered design principles contribute to increased student engagement, learning outcomes, and technology acceptance. Findings demonstrate that virtual laboratories with intuitive UI/UX improve learning effectiveness by up to 68%, enhance student motivation, and increase confidence in conducting practical experiments. We also identify critical design components including clear navigation, real-time feedback, accessibility, and gamification. Our recommendations emphasize the importance of user-centered design approaches in virtual laboratory development to ensure sustainable technology adoption and optimal learning outcomes